MENGANALISIS DAMPAK SAMPAH RUMAH TANGGA TERHADAP PENCEMARAN PESISIR PANTAI MASYARAKAT DUSUN NAMANDOI - Markus Mada; Sumardhiyati R. Syarif; Kartini Rahman Nisa (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2023)
The problem in this research article raises the issue of the household waste of the Namandoi hamlet community which pollutes the coast. Garbage is one of the opportunities for environmental pollution accompanied by a decrease in aesthetic quality. Garbage is not only a government problem but must also be a personal problem for the residents who produce the waste . The number of residents can also affect the increase in the amount of waste. In addition, the behavior of the community to dispose of garbage on the coast is also a habit that can have a negative impact. The purpose of this study was to determine the impact of household waste that pollutes the coast due to people's behavior in disposing of household waste in the coastal area of Namandoi Hamlet. This study uses a qualitative method with descriptive research. Methods of data collection through literature study, field observations, interviews and documentation in Namandoi hamlet, Nanahale village, Talibura district. The results in this study indicate that the community has good knowledge about the behavior of disposing of garbage, but is constrained by the availability of landfill facilities so that many people dispose of household waste in coastal areas. Therefore it is necessary to have village autonomy (according to Law Number 6 of 2014) villages have the autonomy to manage their own households, including managing waste into goods that have economic value for its citizens. Therefore it is necessary to form a special institution based on autonomy villages that can manage waste and provide benefits (such as health insurance and other guarantees) that can stimulate the residents of Namandoi Hamlet to be willing to manage waste.